Vigilante justice [large type] - Lewis, Preston (WHEELER PUBLISHING LARGE PRINT SOFTCOVER WESTERN, 2022)
"Hugh Hampton and his neighbors went to the law but the law looked the other way. Sheriff Johns had no interest in examining the evidence. But someone had blown up the Gillyard place and killed two men. that man was Lemuel Blunt, once owner of the land at Pecan Creek, and had t it fair and square. Now meaner then a junkyard dog he threatened anyone with a rightful claim. As drought burned out Brown county, Texas Blunt takes out his revenge. With the sheriff in his pocket, Blunt thought he could drive them all out and get away with murder. Until Hampton took the law into his own hands and vowed to get justice even if he had to hang for it"--